A review on advances in the development of electrochemical sensors for the detection of anesthetic drugs. Issue 41 (29th September 2022) - Arjun, Ajith Mohan; Krishna, Prasannakumari H.; Nath, Anish R.; Rasheed, P. Abdul
Abstract : It is highly crucial to implement real-time monitoring of anaesthetic drugs to impart quality anaesthetic care. Towards this aspect, this review focuses on the present strategy of electrochemical sensors for the detection of anesthetic drugs. Abstract : Surgeries are a crucial medical intervention that has saved countless lives from time immemorial. To reduce pain during surgeries patients are administered with anesthetic drugs, which cause loss of sensation and thus reduce the pain involved. However, anesthetists control the effects of the drug by depending on pharmacokinetic calculations, which may vary from patient to patient, thus leading to a reduction in the quality of anesthetic care and adverse effects. To avoid these adverse effects, it is highly necessary to implement a real time monitoring of plasma drug concentration, which will adjust the drug infusion and maintain the levels of drug within therapeutic levels. To implement such a system, it is highly essential to analyze current advances in electrochemical sensor systems for different types of anesthetic drugs like opioids, intravenous anesthetics, and neuromuscular blockers. This review focuses on the present strategy of electrochemical sensors implemented for the detection of anesthetic drugs and it helps towards developing a real time drug dispensing system with respect to the plasma concentration of the drug. This analysis will contribute towards establishing highly effective real time drug dispensing systems like the total intravenous anesthesia technique and patient-controlled analgesia. Such systems will lead to better usage of anesthetic drugs and improve the quality of anesthetic care thus making surgeries safer and more painless.